Psychological Skills Training: Practical Guidelines for Athletes, Coaches and Officials - Dugdale, J.; Hodge, K.
Now that you have completed reading this chapter we hope that your interest and knowledge of sport psychology and PST has been enhanced. Psychological skills training is an important aspect of competition preparation for athletes, coaches and officials. The aim of this chapter has been to inform and educate athletes, coaches and officials about PST. Specific issues discussed include the role of the sportpsych consultant, the characteristics of an effective sportpsych consultant and the availability and delivery of sport psychology services within New Zealand. For further information about sport psychology, contact either Sport Science New Zealand or the New Zealand Sport Psychology Association at the addresses noted earlier in this chapter.